A large‐scale genome‐wide association analysis reveals QTL and candidate genes for intramuscular fat content in Duroc pigs. (31st May 2021) - Zhuang, Z.; Ding, R.; Qiu, Y.; Wu, J.; Zhou, S.; Quan, J.; Zheng, E.; Li, Z.; Wu, Z.; Yang, J.
Summary: This study aimed at identifying genomic regions and genes associated with intramuscular fat content (IMF) in Duroc pigs using a weighted single‐step GWAS. Data from 3912 pigs, of which 3770 animals were genotyped with GeneSeek Porcine 50K Bead chip, were used for the association analysis. We identified 19 genomic regions that each explained >1% of the additive genetic variance associated with IMF. Notably, a consistent QTL on SSC7 (117.42–117.92 Mb) was confirmed, explaining 3.70% of the additive genetic variance, and two genes, BDKRB2 and ATG2B, were highlighted as promising candidates for IMF. Two QTL (SSC7, 94.19–94.64 Mb; SSC14, 123.25–123.75 Mb), which harbored MED6 and MAP3K9 genes and TCF7L2 gene respectively, were newly identified as associated with IMF. In conclusion, we identified a consistent QTL and additional genomic regions and genes that contributed to the genetic variance of IMF using a large‐scale sample size of genotyped pigs and genealogical information.